Trends and emerging frontiers of photodynamic therapy for non-melanoma skin cancer (1979–October 2024): a bibliometric analysis - Chen, Qi; Bai, Mingming; Lu, Mingmin; Chen, Jingjing; Wang, Shanshan; Sun, Ping; Li, Linlin; Cai, Hong (Frontiers in Oncology, 2025)
IntroductionPhotodynamic therapy (PDT) is a non-invasive treatment modality for non-melanoma skin cancer (NMSC). This study aims to use bibliometric analysis to explore the research trends and development in the field of PDT for NMSC, identifying key hotspots and emerging directions.MethodsThis study conducted a comprehensive literature search in the Web of Science Core Collection database and applied bibliometric analysis and visualization using tools such as VOSviewer, CiteSpace, and the R package “bibliometrix”.ResultsA total of 358 publications were analyzed, with the USA led in contributions and collaborations, with Yale University being the top institution. The Journal of the American Academy of Dermatology made contributions to the field. Prominent authors included Richard L. Edelson, Arthur H. Rook, and Robert S. Stern. The keywords were categorized into four distinct clusters. The keywords were concentrated into four clusters: Treatment methods and targeted conditions, Cellular and immune responses, Clinical applications and therapeutic management and Techniques and research methodologies. Keywords such as “versus host disease” and “extracorporeal photopheresis” continue to emerge prominently in 2024.ConclusionThis study provides a comprehensive overview of the distribution patterns and key research hotspots in the field of PDT for NMSC. Future research trends should focus on treatment technologies and immune responses.